2,6-Dide-oxy-2,6-imino-l-glycero-d-ido-heptitol. - Jenkinson, S; Booth, K; Newberry, S; Fleet, G; Izumori, K; Morimoto, K; Nash, R; Jones, L; Watkin, D; Thompson, A (2009)
The title mol-ecule, C(7)H(15)NO(5), the major product from selective enzymatic oxidation followed by hydrogeno-lysis of the corresponding azido-heptitol, was found by X-ray crystallography to exisit in a chair conformation with three axial hydroxyl groups. One of the hydroxymethyl groups is disordered over two sets of sites in a 0.590 (3):0.410 (3) ratio. In the crystal, O-H⋯O, O-H⋯(O,O), O-H⋯N and N-H⋯O hydrogen bonding occurs.